School ties: An analysis of homophily in an adolescent friendship network - Eleanor Sanderson
Homophily is the tendency to establish relationships among people who share similar characteristics or attributes. This study presents evidence of homophilic behaviour for an adolescent friendship network of 6,961 links in the West of England. We control for unobserved characteristics by estimating school and individual fixed effects and present evidence on the role of length and closeness of friendships on the degree of homophily. We also exploit the dynamics of the friendship by comparing similarities among existing and future friends. Results indicate that academic achievement, personality, educational aspirations, bad behaviour and mother’s education are essential in the friendship formation process. However, income and parents’ occupational class proved to be insignificant. We also show that the degree of homophily among friends selected from a random process is much lower than that of the observed friendships.Networks, Homophily, Segregation, Friendships, Adolescents